Islamic Psychospiritual Counseling for Parenting and Child Guidance: A Literature Review - Hidayati, Rizqi; Shobahiya, Mahasri (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Abstract Muslim parenting in the digital era faces a gap between predominantly clinical counseling services and the religious needs of families. This article presents a systematic literature review with thematic analysis to formulate an applicable Islamic psychospiritual counseling model for parenting and child guidance. The literature synthesis emphasizes five core values of Islamic parenting: rahmah, hikmah, uswah, ta’dib, and tawazun, along with the integration of attachment theory, exemplary modeling (social learning), and tazkiyatun-nafs as a framework for holistic transformation. The proposed solution is formulated in the RAHMAH model: Regular Assessment, Agreement & Contract, Heartwork Practices, Mentoring by Uswah, Active Communication, and Habit Loop. The derived intervention techniques include religious assessment, guided muhasabah, cognitive restructuring based on verses or hadiths, gratitude exercises, mindful dhikr, journaling, and daily devotional contracts. Key findings indicate that micro-worship practices (prayer and dhikr) are effective as co-regulation between parents and children for emotional regulation and strengthening religious identity. Complementary roles of fathers and mothers, along with extended family and community support, can strengthen the parenting ecosystem. This model offers an operational framework that can be adopted across contexts, with the need for further empirical testing to confirm effectiveness across various age ranges and cultures.